1992
DOI: 10.1128/jvi.66.4.1835-1840.1992
|View full text |Cite
|
Sign up to set email alerts
|

Protective immune response against foot-and-mouth disease

Abstract: The causative agents of foot-and-mouth disease (FMD) are small icosahedral viruses of theAphthovirus group within the Picornaviridae family. There is no evidence that these viruses infect cells of the immune system or otherwise interfere detrimentally with their function; additionally, it has not been possible to relate cytotoxicity reactions against virus-infected cells to the efficacy of the immune response against FMD virus infection. In contrast, there is a close association between FMD virus antibody and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(71 citation statements)
references
References 19 publications
5
62
0
Order By: Relevance
“…However, when the multivariable logistic regression model was retested with village as a fixed effect, there was no significant difference in the titres between villages. This supports the view that vaccineinduced immunity is of short duration, as reported in the literature (Van Maanen and Terpstra, 1989;McCullough et al, 1992). The pre-vaccination anti-SP titres in this study are considered more likely due to previous exposure to FMDV during the 2008-2009 or 2010 outbreaks, rather than the result of vaccination almost 2 years prior to this study.…”
Section: Strategic Vaccination Programmessupporting
confidence: 91%
“…However, when the multivariable logistic regression model was retested with village as a fixed effect, there was no significant difference in the titres between villages. This supports the view that vaccineinduced immunity is of short duration, as reported in the literature (Van Maanen and Terpstra, 1989;McCullough et al, 1992). The pre-vaccination anti-SP titres in this study are considered more likely due to previous exposure to FMDV during the 2008-2009 or 2010 outbreaks, rather than the result of vaccination almost 2 years prior to this study.…”
Section: Strategic Vaccination Programmessupporting
confidence: 91%
“…In silica-treated mice, neutralizing antibody concentrations well over the 90% neutralization titers were required for protection, indicating that in the absence of phagocytosis, protection correlates with neutralization of all the challenge virus. It is likely that efficient protection against FDMV infection by neutralizing antibody at low occupancy is provided by an efficient phagocytosis of sensitized virions, as has been demonstrated for FDMV in vitro (McCullough et al, 1988(McCullough et al, , 1992.…”
Section: J Orthomyxoviruses-influenza Virusmentioning
confidence: 92%
“…The effects of ECMS on IgG isotypes IgG1, IgG2a, IgG2b and IgG3 to FMDV serotypes O and Asia I are shown in observed that a FMD DNA vaccine inducing an immune response in mice can also elicit protection in swine against FMD infection. Humoral immune response has been reported as an important defense mechanism against FMD virus (26,27), and the contribution of antibodies to the major immune defense against the virus is clear (28,29).…”
Section: Fmdv (Serotypes O and Asia I)-specific Igg Isotypesmentioning
confidence: 99%